Reaping cashew free from pests infestation - Bhat, PS; Kumar, NK Krishna (Indian Horticulture, 2019)
The menace of insect pests is the most important factor limiting productivity of cashew in India. Tea mosquito bug and cashew stem- and root-borer are major insect pests throughout the cashew-growing regions of the country. Several innovative approaches involving cultural, biological and chemical measures in suitable combinations are promising in combating menace of these pests. The productivity of cashew can be significantly increased by popularizing and adopting integrated pest management techniques.